Economic convergence in the West African Economic and Monetary Union: a new analysis - Doukouré Charles Fe; Adou Christian Konin; Akra Mohaye Marius N'Guessan (Cogent Economics & Finance, 2024)
This paper uses a structural approach to analyse economic convergence within the West African Economic and Monetary Union (WAEMU) countries. This Regional Economic Community has recorded several postponements of the convergence horizon defined by the Economic Commission. However, it is a framework that is supposed to lead to economic growth and living conditions. So, we estimate a structural convergence model over 1996-2021 for the WAEMU panel of countries. We apply the Generalized Moment Method to address the endogeneity issue in evaluating the coefficient. The analysis confirms no economic convergence within WAEMU countries during this period. This finding means that the economic structures of the WAEMU countries do not come closer over time. Therefore, policymakers must continue implementing initiatives to harmonise regional policies and reinvigorate the regional economic program.
Keywords: C13; O47; 330; Economic convergence; growth; structural characteristics; income disparity; Development